Analisis Tata Kelola Pemerintahan Desa dalam Penanggulangan Kemiskinan Berbasis Pemberdayaan Masyarakat - Aprillia, Angelina Rizza; Handayani, Wiwik (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Poverty is a complex issue that goes beyond just money. It also involves social, political, and how institutions work. Villages, being the smallest level of government, are important in helping people live better lives through good leadership and management. This study looks at how village management helps reduce poverty by giving communities more power and control. To do this, the research used information from recent scientific articles and also studied a real example from Panggungharjo Village in Bantul Regency. The findings show that when villages are open, honest, involve everyone, and work well, it helps empower people and cut down poverty. Village-run businesses, called BUMDes, are 5especially helpful in getting people involved in making money. Empowering communities using their own strengths and with good management creates a lasting path to growth. The study concludes that strong village leadership is key to improving lives and reducing poverty in local areas. These results show that making local institutions stronger, making sure people are held accountable, and involving more community members can make policies work better in villages. In practice, this means social programs can reach the right people more effectively, local businesses can grow in a lasting way, and governments can work together with villagers to create fair development and reduce poverty over time around the world.